Climate Crisis, The : South African and Global Democratic Eco-Socialist Alternatives - Satgar, Vishwas; Project Muse; Project Muse. (Baltimore, Maryland : Project Muse, 2018)
An investigation of emerging eco-socialist alternatives. Capitalisms addiction to fossil fuels is heating our planet at a pace and scale never before experienced. Extreme weather patterns, rising sea levels and accelerating feedback loops are a commonplace feature of our lives. The number of environmental refugees is increasing and several island states and low-lying countries are becoming vulnerable. Corporate-induced climate change has set us on an ecocidal path of species extinction. Governments and their international platforms such as the Paris Climate Agreement deliver too little, too late. Most states, including South Africa, continue on their carbon-intensive energy paths, with devastating results. Political leaders across the world are failing to provide systemic solutions to the climate crisis. This is the context in which we must ask ourselves: how can people and class agency change this destructive course of history? Volume three in the Democratic Marxism series, The Climate Crisis investigates eco-socialist alternatives that are emerging. It presents the thinking of leading climate justice activists, campaigners and social movements advancing systemic alternatives and developing bottom-up, just transitions to sustain life. Through a combination of theoretical and empirical work, the authors collectively examine the challenges and opportunities inherent in the current moment. This volume builds on the class-struggle focus of Volume 2 by placing ecological issues at the centre of democratic Marxism. Most importantly, it explores ways to renew historical socialism with democratic, eco-socialist alternatives to meet current challenges in South Africa and the world.
The climate crisis and systemic alternatives -- The limits of capitalist solutions to the climate crisis -- The anthropocene and imerpeial ecocide -- The employment crisis, just transition and the universal basic income grant -- The rights of Mother Earth -- Buen Vivir: an alternative perspective from the peoples of the global south to the crisis of capitalist modernity -- Challenging the growth paradigm: Marx, Buddha and the pursuit of "happiness" -- Ubuntu and the struggle for an African eco-socialist alternative -- The climate crisis and the struggle for African food sovereignty -- The climate crisis and a "just transition" in South Africa -- Energy, labour and democracy in South Africa -- Capital, climate and the politics of nuclear procurement in South Africa -- Climate jobs at two minutes to midnight -- Deepening the just transition through food sovereignty and the solidarity economy -- Eco-capitalist crises in the "Blue Economy"
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index
Description based on print version record.
Keywords: Greenhouse gases -- Environmental aspects -- South Africa; Climatic changes -- Government policy -- South Africa; Climate change mitigation -- Economic aspects -- South Africa; Human beings -- Effect of climate on; Climatic changes -- Social aspects; Climatic changes -- South Africa; Electronic books